Energy use – in terms of efficiency - Nagy, Orsolya (Acta Agraria Debreceniensis, 2016)
In the recent decades it has become apparent that the human race can lead to a polluting and energy- wasting lifestyle and the depletion of natural resources and an ecological disaster as well.Energy efficiency is the realization of the chance to see a wider use of renewable energy. Renewable energy sources can be found in large quantities in Europe. A proper exploitation of these would be important because of the "traditional" energy sources’s sate is very critical in many ways.The utilization of renewable energy sources depends on many factors. The local natural conditions significantly determine each country's different renewable energy potentials. I find to be important the natural conditions, such as, solar radiation intensity , the number of sunny days per year, the wind conditions , the volume and their energy characteristics of the geothermal power resources , land features , soil and rock quality, the supply of fossil fuels or the nuclear possibilities of energy production. The economic environment is also a major influencing factor for the utilization of renewables. The conditions of price of fossil fuels (natural gas, oil and coal), the price of nuclear fuel production and other energy costs significantly influence the demand for renewables, as well as the level of subsidy and government tax policy. In addition, the international and national programs, objectives, strategies, subsidies and regulatory measures as well as technological factors can have a significant impact.In my paper I point out the opportunities of renewable energy should be given to live. Nowadays the positive effects of their use is undisputed. In addition to the environmentally friendly produced energy, we should strive for energy conservation and energy efficiency as well. These expectations appear in practice, which can be directly perceived by citizens, in fact we should live accordingly. Furthermore, the environmentally relevant regulations of living conditions should appear as environmental demands.